2005
DOI: 10.1002/jhet.5570420613
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxynitrobenzodifuroxan and its salts

Abstract: The synthesis and properties of hydroxynitrobenzodifuroxan (5-nitro[1,2,5]oxadiazolo [3,4-e][2,1,3]benzoxadiazol-4-ol-3,8-dioxide) (1) and its salts (four metal and three amine salts) are described. Crystal structure analyses indicate that the hydroxynitrobenzodifuroxan materials can exist in two forms. One form is the isomer in which the oxy and nitro group are in positions ortho to each other. In the other form, these groups are para to each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…We further add that Scilabra et al [28] have only recently reviewed the importance of the chalcogen bond in crystalline solids, wherein it was briefly speculated that the oxygen atom can nevertheless elicit electrophilicity and hence could form close contacts with nucleophiles. In particular, it was suggested that the crystal of ( S , S )-(−)-2-methylsulfonyl-3-(2-chloro-5-nitrophenyl)oxaziridine [87] is driven by the Cl⋯O chalcogen bond and the crystal of Guanidinium 5-nitro(1,2,5)oxadiazolo(3,4-e)(2,1,3)benzoxadiazole-4-olate3,8-dioxide [88] is driven by the O⋯O chalcogen bond. While Scilabra et al [28] have stressed the presence of O-centered chalcogen bonding in both the crystal systems, such a view might be misleading, since the anion moiety in the latter crystal is stabilized by the guanidinium cation.…”
Section: Discussionmentioning
confidence: 99%
“…We further add that Scilabra et al [28] have only recently reviewed the importance of the chalcogen bond in crystalline solids, wherein it was briefly speculated that the oxygen atom can nevertheless elicit electrophilicity and hence could form close contacts with nucleophiles. In particular, it was suggested that the crystal of ( S , S )-(−)-2-methylsulfonyl-3-(2-chloro-5-nitrophenyl)oxaziridine [87] is driven by the Cl⋯O chalcogen bond and the crystal of Guanidinium 5-nitro(1,2,5)oxadiazolo(3,4-e)(2,1,3)benzoxadiazole-4-olate3,8-dioxide [88] is driven by the O⋯O chalcogen bond. While Scilabra et al [28] have stressed the presence of O-centered chalcogen bonding in both the crystal systems, such a view might be misleading, since the anion moiety in the latter crystal is stabilized by the guanidinium cation.…”
Section: Discussionmentioning
confidence: 99%
“…Very specific bonding patterns can nevertheless elicit oxygen electrophilicity and close contacts with nucleophiles can be found in certain solid systems , (Figure ). In O­(CN) 2 , S­(CN) 2 , and Se­(CN) 2 , two σ-holes are present on chalcogen atoms opposite to the cyano groups, and the respective electrostatic potentials are 31.0, 42.7, and 46.9 kcal·mol –1 .…”
Section: General Features Of Chbsmentioning
confidence: 99%
“…Benzofuroxan derivatives have attracted considerable attention due to their high density, good oxygen balance, good detonation performance, and excellent thermal stability. 7-Amino-6-nitrobenzodifuroxan (ANBDF) is an outstanding representative of the benzofuroxan derivatives. ANBDF has comparable detonation performance with 1,3,5-trinitro-1,3,5-triazinane (RDX), one famous explosive, but does higher density (1.93 g/cm 3 ) and better thermal stability (decomposes around 200 °C) than RDX. The special approximately planar molecule structure with one amino group, one nitro group, and two furoxan rings on the benzene ring and the formation of the intermolecular hydrogen bond between the amino moiety and nitro group make ANBDF possess favorable mechanical sensitivity.…”
Section: Introductionmentioning
confidence: 99%